When the game stands tall [videorecording (DVD)] - Carter, Thomas, 1953-; Caviezel, Jim, 1968-; Chiklis, Michael, 1963-; Ludwig, Alexander, 1992-; Hayes, Neil, 1967- (Sony Pictures Home Enteratinment, 2014)
High school football coach Bob Ladouceur coached the De La Salle High School football team for a record-setting 151-game winning streak, but when the team loses for the first time in twelve years, he and his team are tested.